Artificial Intelligence in Dentistry - A Survey - Rieshy. V1 , L.Keerthi Sasanka2 , R. Gayatri Devi3 , Visalakshi Ramanadhan4 , Dhanraj Ganapathy5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Today’s artificial intelligence is invading our everyday lives such as digital assistants like ALEXA, SIRI.While we may think about sci-fi imagination when heard about artificial intelligence, the future of Artificialintelligence in dentistry is very real. With the enormous increase in the documented information and patientdata, intelligence software and computation of this data is a necessity. While advances in artificial intelligence,neural networking, image recognition, speech recognition, etc have transformed the field of medicine anddentistry in many ways and yet a number of drawbacks, challenges have to be overcome. A self-designedsurvey study was conducted among 100 individuals of the general population. The questionnaire wasdesigned in the manner to assess their knowledge on the treatment and vaccines for COVID-19 infections.The questionnaire contains a set of 10 questions. These questions were distributed through an online surveylink. The study population was well explained about the purpose of this study. The questions were carefullystudied and the responses of each individual has been recorded. The results were statistically analysedthrough an online platform named google forms. The AI has the potential that can be applied in various fieldsof science. Thus most of participants were aware about the usage of AI in dentistry.